Utilization of whey proteins in beverages using Baobab (Adansonia digitata L.), Roselle (Adansonia digitata L.) and Doum (Hyphaene thebaica) fruits - Malaz N. A. M. Saied; Ibtisam E. M. El Zubeir (Food Materials Research)
The loss of valuable nutrient content of the whey proteins obtained from the dairy industry in general is disposed of causing sewage pollution. Therefore, this study aims to utilize the nutrient content of whey proteins to beverages using some Sudanese indigenous fruits: Baobab (Adansonia digitata L.), Roselle (Hibiscus sabdariffa L.) and Doum (Hyphaene thebaica) juices at a rate of 30:70, 50:50 and 70:30% for preparation of beverages. The processed beverages were evaluated for some chemicals, microbial, and sensory properties. Whey proteins enriched with Doum juice revealed significantly (p ≤ 0.05) high-fat level (0.93%), while that enriched with Roselle was significantly (p ≤ 0.05) higher in the protein value (5.97%). Whey proteins enriched with Baobab juice significantly (p ≤ 0.05) revealed a higher value for vitamin C (140.93 mg/100 mL). The values obtained for calcium and phosphorus were significantly (p ≤ 0.05) high in the whey enriched with Roselle juice (8.50 and 1.29 mg/100 mL, respectively). The heat treatment of whey proteins showed significant (p ≤ 0.05) reduction in the total viable bacterial counts. Moreover, the lactic acid bacteria were higher in plain whey proteins followed by those enriched Roselle and Baobab juices. Also, the whey proteins enriched with Roselle juice showed significantly (p ≤ 0.05) the best color. However, the whey proteins enriched with Doum juice significantly (p ≤ 0.05) revealed the best scores for flavor and taste. Hence, the present study concluded that it is possible to use some indigenous Sudanese fruits to utilize the whey proteins as functional food instead of its negative effect on the environment.